Some aspects of application of software agents in information retrieval in virtual– based educational environments - Bakardjieva, Teodora (2006)
The problem of information retrieval has attracted increasing attention in recent years. The amount of information sources via networks has grown and is still rapidly growing. Although existing search engines provide rapid retrieval systems, they give limited assistance to consumers in finding the relevant information they need. Intelligent software agents prove to be the necessary tool in improving the effectiveness and efficiency of retrieval. The paper presents concepts about software agents and discusses their advantages in optimizing the retrieval process. This study explores the application of software agents in information retrieval processes in web-based applications for online learning systems. The research was done at Technical University of Varna, and an interactive system new for Bulgaria is proposed.